Angiotensin-(1–7) upregulates central nitric oxide synthase in spontaneously hypertensive rats - Cerrato, Bruno Diego (2012)
Increased blood pressure in hypertension is hypothesized to be caused by high sympathetic nervous system (SNS) activity. Since Ang (1–7) exerts an inhibitory neuromodulatory effect on the SNS through a NO-mediated mechanism, we tested the hypothesis that Ang (1–7) alters centrally nitric oxide synthase (NOS) activity and expression in spontaneously hypertensive rats (SHR). Since NOS activity is altered in relation to the development of hypertension in rats, we evaluated the effect of Ang-(1–7) on hypothalamic NOS activity in two different ages in SHR, corresponding to a prehypertensive phase (3–4 weeks) and a established hypertension (13–14 weeks) and compared with age-matched Wistar-Kyoto (WKY) rats. NOS activity was measured by the conversion of [3 H]L-arginine to citrulline . Ang-(1–7) caused an impairment in NOS activity in prehypertensive SHR (26± 4% reduction), while it induced an increase in NOS activity at established hypertension (48 ± 9% increase). In contrast, Ang-(1–7) did not modify NOS activity in age-matched WKY rats. In another set of experiments, Ang-(1–7) was injected into the anterior hypothalamic area, mean arterial blood pressure (MAP) was registered and after 30, 60 and 180 min nNOS expression was evaluated by Western-blot. Ang-(1–7) decreased MAP after 10 min of injection and this effect was blocked by a NOS inhibitor. nNOS expression increased after 180 min of Ang-(1–7) intrahypothalamic injection in both WKY and SHR (WKY: 3.6-fold increase above basal; SHR: 1.85-fold increase above basal). Our results suggest that Ang-(1–7) upregulates hypothalamic NOS in a hypertensive state as a compensatory and protective mechanism to combat hypertension.